2022
DOI: 10.3390/children9050729
|View full text |Cite
|
Sign up to set email alerts
|

Use of Visual Pedagogy to Help Children with ASDs Facing the First Dental Examination: A Randomized Controlled Trial

Abstract: Autism Spectrum Disorders (ASDs) are neurodevelopmental disorders that don’t have a direct effect on oral health, but severe difficulties in oral hygiene and dental procedures expose people with ASDs to an increased risk of oral diseases. This RCT aimed to evaluate which pedagogical tool was the best to prepare children with ASDs for their first dental examination, either video or photo aids. Two different criteria were used to evaluate their efficacy: the achieved steps into which the procedure was divided (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Adapting to the individualised needs of Autistic patients can include electronic communication systems that prepare the patients for their experience at a dental clinic and address their fear of the dental environment [ 46 , 47 ]; adapting the environment to the sensory needs of Autistic individuals to reduce physical and behavioral stress [ 7 , 11 ]; familiarisation by using visual model techniques [ 48 ]: as well as pre-treatment questionnaires and social stories to enable the Autistic patient and the dental practitioner prepare for their dental visit [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adapting to the individualised needs of Autistic patients can include electronic communication systems that prepare the patients for their experience at a dental clinic and address their fear of the dental environment [ 46 , 47 ]; adapting the environment to the sensory needs of Autistic individuals to reduce physical and behavioral stress [ 7 , 11 ]; familiarisation by using visual model techniques [ 48 ]: as well as pre-treatment questionnaires and social stories to enable the Autistic patient and the dental practitioner prepare for their dental visit [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each of them should be used when needed and adapted to the patient's capability for obtaining collaboration: This is the base for continuing dental cures for a lifetime ( 44 , 45 ). Behavioral intervention with visual tools, either video or photograph, has been successfully used to prepare children for the first dental examination ( 46 ) and for tooth brushing ( 47 ) and, either culturally adapted or not, may improve oral health status ( 48 ). Furthermore, virtual reality and video modeling have been used successfully to improve oral hygiene ( 49 , 50 ), and apps have been found to be more effective than pictures in accepting some procedures ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cirio (2022)[ 24 ] opined that successful dental healthcare for autistic children has the requirement of close cooperation and a good relationship between parents and dentists. One must try to reduce the waiting time for autistic children before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cirio et al . (2022)[ 27 ] evaluated the effectiveness of both video and photograph (pedagogical tools) and concluded that the behavioral intervention through visual aids should be used as a strategy to prepare patients with ASDs for their first dental examination.…”
Section: Discussionmentioning
confidence: 99%